Development of technique and program for analysis of options for transition to a closed hot-water supply scheme for heat supply systems - F. N. Gazizov; I. G. Akhmetova (Известия высших учебных заведений: Проблемы энергетики)
The article describes the prerequisites for development of methodology for integrated assessment of options for transition to a closed hot-water supply scheme. For analysis of promising options for transition to a closed system of hot water supply, criteria have been proposed that influence the choice of possible solutions. Block diagrams of boundary conditions and independent variables were created. A pyramid of indicators which affect the operating costs of heating system over 25 years of its operation was formulated. A method and a program for selecting the optimal transition scheme to a closed hot-water supply system with calculation of weighting factors have been developed.